A feasibility study of X‐ray phase‐contrast mammographic tomography at the Imaging and Medical beamline of the Australian Synchrotron. (15th October 2015) - Nesterets, Yakov I.; Gureyev, Timur E.; Mayo, Sheridan C.; Stevenson, Andrew W.; Thompson, Darren; Brown, Jeremy M. C.; Kitchen, Marcus J.; Pavlov, Konstantin M.; Lockie, Darren; Brun, Francesco; Tromba, Giuliana
Abstract : Results are presented of a recent experiment at the Imaging and Medical beamline of the Australian Synchrotron intended to contribute to the implementation of low‐dose high‐sensitivity three‐dimensional mammographic phase‐contrast imaging, initially at synchrotrons and subsequently in hospitals and medical imaging clinics. The effect of such imaging parameters as X‐ray energy, source size, detector resolution, sample‐to‐detector distance, scanning and data processing strategies in the case of propagation‐based phase‐contrast computed tomography (CT) have been tested, quantified, evaluated and optimized using a plastic phantom simulating relevant breast‐tissue characteristics. Analysis of the data collected using a Hamamatsu CMOS Flat Panel Sensor, with a pixel size of 100 µm, revealed the presence of propagation‐based phase contrast and demonstrated significant improvement of the quality of phase‐contrast CT imaging compared with conventional (absorption‐based) CT, at medically acceptable radiation doses.